Bibliometric Analysis of the Integration of Da'wah Values and Digital Literacy in Formal Islamic Education in Yogyakarta 2020-2024 - Wicaksono, Ardhitya Furqon; Pratama, Yoga Anjas; Rahayu, Katty Febriliani; Waris, Abdul (Scidac Plus, 2025)
The rapid digital transformation has significantly reshaped education, communication, and religious practices, including the landscape of formal Islamic education. Traditional da’wah methods, such as mosque-based preaching, are increasingly supplanted by digital platforms like social media and podcasts, necessitating innovative approaches to engage Millennials (born 1981-1996) and Generation Z (born 1997-2012). This study maps trends in the integration of da’wah values and digital literacy within Yogyakarta’s Islamic education system from 2020 to 2024 through a bibliometric analysis guided by the PRISMA protocol. From an initial pool of 150 articles retrieved from Scopus, SINTA, and Google Scholar, 68 were included following rigorous screening and eligibility assessment. Findings indicate a publication surge in 2022, reflecting accelerated post-pandemic digital adoption. TikTok and Instagram emerged as the dominant platforms for digital da’wah (featured in 65% of studies), displacing conventional preaching methods. While many madrasahs have begun integrating digital literacy into curricula, 45% still lack technical implementation guidelines, and only 30% of studies discuss educator training initiatives. Bibliometric mapping highlights strong thematic linkages between “digital da’wah,” “Islamic education transformation,” and “social media,” signalling a pedagogical paradigm shift. However, the scarcity of evaluative studies (only 8%) reveals a critical need for field-based research to assess the effectiveness of these digital strategies. This study offers a systematic literature foundation to inform curriculum design and advocates for collaborative policymaking among educators, scholars, and government bodies to advance digitally responsive Islamic education.